2021
DOI: 10.22605/rrh6457
|View full text |Cite
|
Sign up to set email alerts
|

Severity of climacteric symptoms among Peruvian women from an urban coastal community and a rural Andean community

Abstract: Introduction: The aim of this study was to evaluate the severity of climacteric symptoms among two Peruvian communities, adjusted for sociodemographic and clinical variables in climacteric women. Methods: A cross-sectional study was conducted on 90 subjects Rural and Remote Health rrh.org.au

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In contrast, the most common symptoms experienced by Spanish and Peruvian urban and rural women were different. Hot flashes/sweating was commonly reported among Spanish women, whereas muscle/joint pain and fatigue were the most typical symptoms reported among rural Peruvian women and urban Peruvian women, respectively 13,14 . These two studies also compared the prevalence of menopausal symptoms between urban and rural women and demonstrated that the frequency of menopausal symptoms was higher, and the severity of menopausal symptoms was lower among the urban women than among the rural women 13,14 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast, the most common symptoms experienced by Spanish and Peruvian urban and rural women were different. Hot flashes/sweating was commonly reported among Spanish women, whereas muscle/joint pain and fatigue were the most typical symptoms reported among rural Peruvian women and urban Peruvian women, respectively 13,14 . These two studies also compared the prevalence of menopausal symptoms between urban and rural women and demonstrated that the frequency of menopausal symptoms was higher, and the severity of menopausal symptoms was lower among the urban women than among the rural women 13,14 .…”
Section: Discussionmentioning
confidence: 98%
“…13,14 These two studies also compared the prevalence of menopausal symptoms between urban and rural women and demonstrated that the frequency of menopausal symptoms was higher, and the severity of menopausal symptoms was lower among the urban women than among the rural women. 13,14 This disparity may be explained by the difference in factors such as ethnicity, diet, socioeconomic status, lifestyle, and geographical situation. Low education level, overweight and obesity, vegetarian diet, and living separate from one's husband are factors that are more prevalent in rural China than urban China and were demonstrated to be positively associated with MPS symptoms.…”
Section: Menopausal Symptoms In Urban Rural Womenmentioning
confidence: 99%
See 2 more Smart Citations